Firm Performance Following IPO - Satrio Rifky Aprilianto; Nofal , Mohammad; Bidin, Cici Rianty K; Anisah, Anisah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the financial performance of 59 companies that conducted Initial Public Offerings (IPOs) on the Indonesia Stock Exchange in 2022. Using a comparative quantitative approach, it analyzes financial indicators from one year before and after the IPO. Performance metrics include profitability (ROA, ROE, NPM), leverage (DAR), activity (TATO), and asset growth (AG). The Wilcoxon Signed-Rank Test and t-test were used to assess differences. Results indicate a decline in profitability, leverage, activity, and asset growth post-IPO, suggesting that IPOs may not immediately enhance financial performance.